Політика "позитивної дії" щодо афроамериканців у США: історична ретроспектива - Петраускас, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
У статті досліджуються передумови, основні етапи та процес
еволюції політики «позитивної дії» у США в др. пол. ХХ ст. — на поч.
ХХІ ст., висвітлюються особливості її застосування щодо афроамериканського населення. Здійснюється аналіз урядових документів, що
стали основою нового підходу американської влади щодо расового питання. Ідея «позитивних дій» розвивалася американськими інтелектуалами, громадськими діячами та політиками впродовж ХХ ст. і
створила фундамент для цілеспрямованого національного внутрішньополітичного курсу. Політика «позитивної дії», реалізована у др. пол.
ХХ ст., стала комплексом урядових заходів, спрямованих на розв’язання
внутрішніх суспільно-політичних проблем, пов’язаних із афроамериканською громадою. Складність, суперечливість та багатогранність расових взаємовідносин у США зумовили активну наукову та суспільну
дискусію щодо необхідності такої політики. У статті звертається
увага на успішні приклади застосування «позитивної дії» щодо темношкірого населення США у сфері працевлаштування та освіти.
Аналізується роль цієї політики в подоланні проблем расових взаємовідносин в американському суспільстві на сучасному етапі. Порівнюються
різні погляди щодо необхідності застосування політики «позитивної дії»
до афроамериканців на сучасному етапі. The article examines the preconditions, the main stages and the process of
evolution of Affirmative Action in the United States. Affirmative action is a set
of laws, policies, guidelines, and administrative practices intended to correct
any form of discrimination. These include government-mandated, governmentsanctioned
and voluntary private programs that tend to focus on access to
education and employment, granting special consideration to historically
excluded groups based on race, such as African Americans.
Affirmative Action idea was developed by American intellectuals, public
figures and politicians during the twentieth century. The article also analyzes
government documents that have become the basis of a new approach to US
policy on racial issues. The idea of Affirmative action policies first emerged
from debates over non-discrimination policies in the 1940s and during
the Civil Rights Movement. These debates led to federal executive orders
requiring nondiscrimination in the employment policies of some government
agencies and contractors in the 1940s and onward, and to Title VII of the Civil
Rights Act of 1964 which prohibited racial discrimination.
So, Affirmative action policy for African Americans in the US arose in the
1960s as a result of the movement of the black people for their rights. To
overcome racial problems the United States Government was forced to
introduce completely new course which aimed to prohibit discrimination
against African Americans.
The article analyzes various approaches to Affirmative action towards
African Americans. The complexity, controversy and versatility of racial
relationships in the United States led to the active scientific and social debate
about such a policy. Opponents of Affirmative action argue that these policies
amount to reverse discrimination which entails favoring one group over
another basing on racial preference rather than achievement, and many
believe that the diversity of current American society suggests that affirmative
action policies succeeded and are no longer required. In particular, policies
adopting racial quotas or gender quotas have been criticized as a form of
reverse discrimination.